La apertura al mundo y el mundo rural, doscientos años después - Djenderedjian, Julio (2016)
El texto repasa el impacto de la apertura comercial al mundo traída por la Revolución en el Río de la Plata. Se enfoca en las condiciones que el nuevo paradigma trajo al mundo rural y en las consecuencias para los distintos espacios de esa región. Se trata de un ensayo basado en fuentes éditas, inéditas y bibliografía.
The text addresses the impact of the commercial opening to the World in the Rio de la Plata region, which started shortly before the May Revolution of 1810. It is focused on the conditions brought to the rural world by that new paradigm, and on the outcomes for the different areas inside that region. This is an essay build on published and non-published sources, as well as bibliography.
Keywords: Apertura al mundo; Revolución; Mundo rural; Producción rural; Opening to the World; Revolution; Rural world; Rural production; 19th. Century; Río de la Plata